2006
DOI: 10.1016/j.ssi.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

LiMn2−xTixO4 spinel-type compounds (x≤1): Structural, electrical and magnetic properties

Abstract: LiMn 2-x Ti x O 4 compounds with 0 ≤ x ≤ 1 were prepared by solid state reaction and Pechini technique. Powder X-ray diffraction showed that all samples crystallize with the spinel crystal structure (S.G. Fd 3 m). The cubic unit-cell parameter increases with Ti content.The influence of the Ti content and cationic distribution on the magnetic properties of the compounds was studied by measuring the temperature and magnetic field dependences of the magnetization : substitution by non magnetic d 0 Ti 4+ ions appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…However, neutron diffraction measurements have shown that Li and Ti ions show a partial inverted distribution in LiMnTiO 4 over the tetrahedral and octahedral sites, although a more recent study has suggested that the Mn ion is disordered between these sites. [18] The same situation occurs in LiFeTiO 4 with Li and Fe ions. [17,22] -1 more stable than the normal spinel, hence the energy difference between ramsdellite and spinel forms increases by the same amount to 36.5 kJ mol -1 , which is the same energy difference found in the Cr system (see Figure 3).…”
Section: Computational Analysis Of the Litimo 4 (S) ↔ Litimo 4 (R) Trmentioning
confidence: 82%
See 1 more Smart Citation
“…However, neutron diffraction measurements have shown that Li and Ti ions show a partial inverted distribution in LiMnTiO 4 over the tetrahedral and octahedral sites, although a more recent study has suggested that the Mn ion is disordered between these sites. [18] The same situation occurs in LiFeTiO 4 with Li and Fe ions. [17,22] -1 more stable than the normal spinel, hence the energy difference between ramsdellite and spinel forms increases by the same amount to 36.5 kJ mol -1 , which is the same energy difference found in the Cr system (see Figure 3).…”
Section: Computational Analysis Of the Litimo 4 (S) ↔ Litimo 4 (R) Trmentioning
confidence: 82%
“…However, experimen- tal results indicate that in the case of M = Cr, Mn and Fe some transition metal ions are located in the tetrahedral sites. [15][16][17][18] Note that in the first part of this computational study we have not considered the degree of inversion. In view of the data in Tables 1 and 2, it can be concluded that, generally speaking, the calculation method allows a correct prediction of the cell parameters, with differences of around 2-4 % that are typical for state-of-the-art approximations to density functional theory in transition metal oxides.…”
Section: Computational Analysis Of the Litimo 4 (S) ↔ Litimo 4 (R) Trmentioning
confidence: 99%
“…The XRD patterns for all three samples exhibit only the characteristic diffraction peaks for a well-crystallized spinel structure with Fd-3m symmetry. Rietveld refinements of these XRD showed that [24][25][26][27] . In addition, the absence of TiO 2 peaks in the XRD patterns for the TSC-LMO sample is probably caused by the low concentration or the amorphous state of the ALD TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to solve these problems, people have proposed an effective strategy [8][9][10] to substitute Mn 3+ , which contributes to improve conductivity of the cathode materials as well as the electrochemical performance of the battery. Krins et al 11 and Wu et al 12 doping Ti 4+ greatly improved the electrochemical property of LiMn2O4. Because the binding energy of Cr-O (1142 KJ/mol) is much higher than that of Mn-O (946 KJ/mol) [13][14][15] , doping Cr 3+ propelled the formation of a stable three-dimensional structure and decreasing of the dissolved load of Mn 2+ , which weakened the Jahn-Teller effect.…”
Section: Introductionmentioning
confidence: 98%